2011
DOI: 10.1159/000319839
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sandwich ELISA to Measure Exposure to Occupational Cow Hair Allergens

Abstract: Background: Cow hair and dander are important inducers of occupational allergies in cattle-exposed farmers. To estimate allergen exposure in farming environments, a sensitive enzyme immunoassay was developed to measure cow hair allergens. Methods: A sandwich ELISA was developed using polyclonal rabbitantibodies against a mixture of hair extracts from different cattle breeds. To assess the specificity of the assay, extracts from other mammalian epithelia, mites, molds and grains were tested. To validate the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 69 publications
3
42
0
Order By: Relevance
“…In stables, the levels of bovine hair allergens in airborne dust can reach immensely high values. In our previous report, the median allergen concentration was 14 mg/g dust, and allergen levels differed by about 100-fold between cow stables (all with Simmental cattle), ranging from 5,000 to 560,000 μg/m 2 [11] . It is likely that some proportion of the airborne allergen produced by livestock settles back onto the fur during the sedimentation process.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In stables, the levels of bovine hair allergens in airborne dust can reach immensely high values. In our previous report, the median allergen concentration was 14 mg/g dust, and allergen levels differed by about 100-fold between cow stables (all with Simmental cattle), ranging from 5,000 to 560,000 μg/m 2 [11] . It is likely that some proportion of the airborne allergen produced by livestock settles back onto the fur during the sedimentation process.…”
Section: Discussionmentioning
confidence: 75%
“…Bovine hair allergen concentrations were determined via a sandwich ELISA as described by Zahradnik et al [11] . The assay was developed using affinity-purified polyclonal antibodies against the total soluble antigen spectrum extracted from bovine hair.…”
Section: Bovine Hair Allergen Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have quantitatively assessed bovine allergens in the environment, and they all found high levels of allergens in cow stables (Berger et al, 2005;Virtanen et al, 1988;Zahradnik et al, 2011). Zahradnik et al (2011) reported median levels of bovine hair allergen in cow stables to be 51,700 g/m 2 .…”
Section: Introductionmentioning
confidence: 99%